Facilitating organizational learning through agent-based modeling and simulation experimentation. Issue 6 (12th September 2016) - Baškarada, Saša; Chandran, Arvind; Shokr, Mina; Stewart, Christopher
Abstract : Purpose: In addition to requiring high absorptive capacity, contemporary organizations operating in highly dynamic and complex environments also require the ability to create knowledge internally, within the organization. While the organizational learning (OL) literature has produced a plethora of theories and frameworks, there has been relatively little empirical research on specific mechanisms for internal knowledge generation. Accordingly, this paper aims to answer calls for more research on mechanisms for internal generation of organizational knowledge. Design/methodology/approach: This paper is an in-depth case study in the Australian Defence Organisation (ADO). Findings: The paper presents a cyclical eight-stage knowledge generation process and demonstrates how agent-based modeling and simulation (ABMS) may be used to facilitate OL. Originality/value: By detailing an in-depth case study of an ABMS mechanism for internal knowledge generation in the ADO, this paper provides a novel and relevant contribution to the OL literature.